2011
DOI: 10.1007/s10384-011-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trabeculectomy on ocular and corneal higher order aberrations

Abstract: Ocular coma-like and total aberrations were significantly increased at 1 month after trabeculectomy with a limbal-based conjunctival flap, but they had returned to normal levels by 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Several studies have demonstrated that ocular surgeries such as intraocular lens implantation and cataract extraction [ 9 - 11 ], scleral buckling [ 12 ], and pterygium excision [ 13 ] may result in changes in the refractive state or higher-order aberrations [ 14 - 16 ] in the affected eye. In the present study, consistent with previous studies, we report similar changes in ocular higher-order aberrations 1 month postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that ocular surgeries such as intraocular lens implantation and cataract extraction [ 9 - 11 ], scleral buckling [ 12 ], and pterygium excision [ 13 ] may result in changes in the refractive state or higher-order aberrations [ 14 - 16 ] in the affected eye. In the present study, consistent with previous studies, we report similar changes in ocular higher-order aberrations 1 month postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attributed these alterations in visual acuity to changes in corneal contour, anterior chamber depth, axial length of the globe, and thickness of the crystalline lens [ 6 , 18 - 23 ]. Another study demonstrated with vector analysis that the cylinder component of refraction was increased by 1.4 D; however, the vector power of surgically induced refractive change at 1 month postoperatively did not significantly correlate with corneal coma-like, spherical-like, or total RMS, suggesting that changes other than anterior corneal aberration, such as internal optics of the eye, play a role in the changes in higher-order aberrations postoperatively[ 14 ]. Francis et al [ 23 ] reported a decrease in the axial length of the globe following trabeculectomy that was more prominent 1 week and 1 month after surgery, and suggested over-filtration as the explanation for their finding; however, similar to our findings, Fukuoka et al [ 14 ] have shown that despite the stability of IOP from 1 month to 3 months postoperatively, the values of ocular coma-like, spherical-like, and total higher order aberrations changed during this time period and reached values similar to preoperative measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with corneal steepening, higher order aberrations including ocular coma‐like and total aberrations increase significantly at one month post‐trabeculectomy but return to normal levels by three months . The corneal coma‐like and total aberrations remain unchanged during the first three post‐operative months and there is no significant correlation between the ocular and corneal coma‐like aberrations and between the ocular and corneal total aberrations at one month post‐trabeculectomy .…”
Section: Keratometric Changesmentioning
confidence: 95%
“…В литературе также встречаются единичные сообщения, посвященные детальному анализу рефракционных изменений роговицы в хирургии глаукомы [8][9][10]. Хирургические манипуляции на фиброзной оболочке глаза неизбежно приводят к вторичным изменениям его оптической структуры [11,12].…”
Section: клинические исследованияunclassified